Point-of-Care Tests for Hepatitis B: An Overview - Yinzong Xiao; Alexander J. Thompson; Jessica Howell (Cells, 2020)
Despite the heavy disease burden posed by hepatitis B, around 90% of people living with hepatitis B are not diagnosed globally. Many of the affected populations still have limited or no access to essential blood tests for hepatitis B. Compared to conventional blood tests which heavily rely on centralised laboratory facilities, point-of-care testing for hepatitis B has the potential to broaden testing access in low-resource settings and to engage hard-to-reach populations. Few hepatitis B point-of-care tests have been ratified for clinical use by international and regional regulatory bodies, and countries have been slow to adopt point-of-care testing into hepatitis B programs. This review presents currently available point-of-care tests for hepatitis B and their roles in the care cascade, reviewing evidence for testing performance, utility, acceptability, costs and cost-effectiveness when integrated into hepatitis B diagnosis and monitoring programs. We further discuss challenges and future directions in aspects of technology, implementation, and regulation when adopting point-of-care testing in hepatitis B programs.